Compound Heterozygous Mutations in the BBS-1 Gene and its Clinical Presentation: A Case Report - Michelen-Gómez, Eduardo; Guardiola-Dávila, Gabriel; Izquierdo, Natalio J. (Puerto Rico Health Sciences Journal, 2021)
Compound heterozygous mutations, where two distinct mutated alleles are present within a particular gene, can give rise to the Bardet-Biedl syndrome (BBS). There is limited evidence suggesting that some compound heterozygotes can present with milder phenotypic characteristics than homozygotes. We report on the clinical characteristics of a 22-year-old Puerto Rican male who was compound heterozygous for the Bardet-Biedl syndrome type 1. Our patient had deteriorating visual acuity since early childhood. Clinical and ophthalmic examination revealed retinal dystrophy, polydactyly, and very mild learning disabilities. No additional systemic complications commonly observed in patients with the BBS were present. Allele-specific testing and DNA sequencing revealed compound heterozygous mutations (M390R and E549X) in the BBS1 gene. Our findings could suggest that patients who are compound heterozygotes for these specific BBS mutations can exhibit milder clinical signs than homozygous patients.